THE INFLUENCE OF ORGANIZATIONAL, ECONOMIC MEASURES ON OCCUPATIONAL SAFETY AND ERGONOMIC INDICATORS ON THE LEVEL OF INJURY AT METALLURGICAL PLANTS - Manidina, Yevheniia; Ryzhkov, Vadim; Belokon, Karina; Vodennikova, Oksana; Tsymbal, Victor (Scientific Journal "Metallurgy", 2022)
The Law of Ukraine “On Occupational Safety” emphasizes that the principle of state policy is based on the principles of priority of life and health of employees, full responsibility of the employer for the creation of appropriate, safe and healthy working conditions. One of the markers of the level of occupational protection and overall health and safety at industrial enterprises is the level of injuries. According to the International Labor Organization, about 340 million accidents at work and 160 million cases of occupational diseases occur annually in the world. The world community has long understood that investing in occupational safety measures and thus preventing occupational injuries is more cost-effective than having the costs associated with accidents and eliminating the consequences of accidents and industrial accidents. Today, in accordance with the Law of Ukraine “On Occupational Safety” for the enterprises of our state, the cost of labor protection is not less than 0.5 percentage points of the labor remuneration fund for the previous year. Identification of the main causes of the occurrence of accidents at the enterprise allows to establish the priority and efficiency of measures for the protection of human rights and as a consequence their economic feasibility. Analysis of statistical data for recent years on the level of injuries in enterprises of Ukraine has shown that the main causes of accidents are the organizational ones. Practice also shows that high-quality initial training on labor protection, compliance with ergonomic requirements for job placement provide a significant reduction in injuries at metallurgical enterprises.